2021
DOI: 10.1186/s12866-020-02002-3
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle modifications result in alterations in the gut microbiota in obese children

Abstract: Background The association between the gut microbiota and pediatric obesity was analyzed in a cross-sectional study. A prospective study of obese children was conducted to assess the gut microbial alterations after a weight change. We collected fecal samples from obese children before and after a 2-month weight reduction program that consisted of individual counseling for nutritional education and physical activity, and we performed 16S rRNA gene amplicon sequencing using an Illumina MiSeq plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
49
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 69 publications
(59 reference statements)
4
49
0
3
Order By: Relevance
“…Our data show that gut microbial richness, as measured with the Shannon Index, is significantly reduced following early life CAF, but not SUG, diet, an outcome that was actually exacerbated following the healthy dietary intervention. This outcome is consistent with other studies in which microbial richness was reduced after the removal of high-fat, high-sugar diets (Fülling et al, 2020;McNamara et al, 2021) or reduced adiposity following lifestyle modifications (eating breakfast, avoiding sugar-sweetened beverages, decreasing processed foods rich in animal fat or lengthening meal duration, and implementing more exercise) (Cho, 2021). Composition of the gut microbiota was significantly distinct from controls immediately after either the adolescent CAF or SUG exposure period analyzed with PERMANOVA tests.…”
Section: Discussionsupporting
confidence: 90%
“…Our data show that gut microbial richness, as measured with the Shannon Index, is significantly reduced following early life CAF, but not SUG, diet, an outcome that was actually exacerbated following the healthy dietary intervention. This outcome is consistent with other studies in which microbial richness was reduced after the removal of high-fat, high-sugar diets (Fülling et al, 2020;McNamara et al, 2021) or reduced adiposity following lifestyle modifications (eating breakfast, avoiding sugar-sweetened beverages, decreasing processed foods rich in animal fat or lengthening meal duration, and implementing more exercise) (Cho, 2021). Composition of the gut microbiota was significantly distinct from controls immediately after either the adolescent CAF or SUG exposure period analyzed with PERMANOVA tests.…”
Section: Discussionsupporting
confidence: 90%
“…Our data show that gut microbial richness, as measured with the Shannon Index, is significantly reduced following early life CAF, but not SUG, diet, and that this effect was actually greater in animals that underwent the healthy dietary intervention compared to those that did not. This outcome is consistent with other studies in which microbial richness was reduced after the removal of high-fat, high-sugar diets [52,53] or reduced adiposity following lifestyle modifications (eating breakfast, avoiding sugar-sweetened beverages, decreasing processed foods rich in animal fat or lengthening meal duration, and implementing more exercise) [54]. Composition of the gut microbiota was significantly distinct from chow-fed rats immediately after either the adolescent CAF or SUG exposure period analyzed with PERMANOVA tests.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, Olivares et al observed differences in gut microbiome of adults depending on weight status, finding a rise in the genus Bifidobacterium and a decrease in Prevotellaceae, Faecalibacterium, and Eubacteriumrectale in participants with normal weight compared to those who had overweight or obesity. 29 In addition, the phylum Bacteroidetes 24,25,28,30 and the genus Bifidobacterium 27 are underrepresented in gut microbiota of children with overweight or obesity compared to the microbiota of children with normal-weight (Table 1), where lifestyle changes (diet/physical activity) may affect fecal microbiota. 30 In this context, a multicenter prospective cohort trial called TEDDY study was designed, with the objective of identifying those environmental factors that triggered or protected against type 1 diabetes.…”
mentioning
confidence: 99%